INTEGRATION OF LASER AND OPTO-GALVANIC METHODS IN ENVIRONMENTAL MONITORING SYSTEMS OF TECHNOGENIC FACILITIES - SIKORA, Liubomyr; LYSA, Nataliia; FEDEVYCH, Olga (Computer systems and information technologies, 2026)
The current stage of development of the electric power, chemical, mechanical engineering, and printing industries is characterized by the extensive use of a wide range of resource components, including coal, oil, natural gas, paints and coatings, and polymers, which are marked by increased environmental aggressiveness. Highly intensive production operating modes, driven by market demands, lead to a significant growth in resource consumption within energy-intensive technological processes. This, in turn, results in increased concentrations of dust as well as harmful gaseous and liquid emissions released into the atmospheric and aquatic environments, causing an overall deterioration of environmental conditions. At the same time, real-time assessment of the environmental state is often complicated by the limited capabilities of data acquisition and processing using conventional measurement methods. A considerable number of information and measurement systems, laboratory methods, and analytical instruments exist for determining the concentration of harmful emissions in the atmosphere, soils, and water bodies of ecosystems; however, most of these approaches are based on environmental sampling followed by laboratory analysis, which requires a certain amount of time. In technological systems, control and measurement devices and sensors are employed; nevertheless, they do not ensure the measurement of critical production process parameters during the stages in which pollutant flows are generated. Typical examples include emissions of combustion products in boilers of thermal power plant units and municipal systems, as well as in construction, transport and aviation sectors, oil refining and gas industries, and chemical plants of both public and private ownership. In this context, the problem of environmental monitoring—namely, the development of systems, structures, and sensors—is technically urgent and socially significant. Accordingly, the development of information technologies for data acquisition in environmental monitoring of ecological media (atmosphere, water, and soils), based on opto-galvanic pollution control methods and laser remote sensing techniques for measuring the concentration of harmful gas emissions, combustion products, and dust, is highly relevant, as these technologies enable continuous monitoring of pollutant concentrations.